Chemoenzymatic Synthesis of Advanced Intermediates for Formal Total Syntheses of Tetrodotoxin. (30th May 2018) - Baidilov, Daler; Rycek, Lukas; Trant, John F.; Froese, Jordan; Murphy, Brennan; Hudlicky, Tomas
Abstract: Advanced intermediates for the syntheses of tetrodotoxin reported by the groups of Fukuyama, Alonso, and Sato were prepared. Key steps include the toluene dioxygenase mediated dihydroxylation of either iodobenzene or benzyl acetate. The resulting diene diols were transformed into Fukuyama's intermediate in six steps, into Alonso's intermediate in nine steps, and into Sato's intermediate in ten steps.